2011
DOI: 10.1111/j.1540-6237.2011.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial Threat or Racial Contact? How Race Affected Third‐Party Presidential Voting in the Antebellum North*

Abstract: Objective. In this study, the “racial threat” and “racial contact” hypotheses are evaluated in relation to voting for the Liberty and Free Soil Parties in the North during the 1840s. Methods. Regression models are used to predict the effect of county‐level black populations on Liberty and Free Soil vote percentages in relation to types of employment. Results. Racial threat occurred in high manufacturing counties, but racial contact/threat emerged in more agricultural counties. The effects vary by party and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, other researchers who have compared varied approaches to measuring diversity maintain that ELF remains the best measure (Neumann and Graeff, 2013; Schaeffer, 2013). Increasingly, there are findings suggesting that the negative attitudes of majority-group members toward minority-group members are attenuated once the minority group is integrated enough into society for contact to increase (Chamberlain, 2011; Fullerton and Dixon, 2009; Steele and Perkins, 2018; Stein et al, 2000). Finally, research on immigration in urban West Africa suggests that cultural similarities between immigrants and native populations may actually disrupt immigrant integration (Adida, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other researchers who have compared varied approaches to measuring diversity maintain that ELF remains the best measure (Neumann and Graeff, 2013; Schaeffer, 2013). Increasingly, there are findings suggesting that the negative attitudes of majority-group members toward minority-group members are attenuated once the minority group is integrated enough into society for contact to increase (Chamberlain, 2011; Fullerton and Dixon, 2009; Steele and Perkins, 2018; Stein et al, 2000). Finally, research on immigration in urban West Africa suggests that cultural similarities between immigrants and native populations may actually disrupt immigrant integration (Adida, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Another line of scholarship blends these two theories, suggesting that there is a curvilinear relationship between racial threat, inter-group contact, and discriminatory attitudes. Studies of the United States have found that negative attitudes of the majority group toward the minority group increase when the minority population is larger; in contrast, when the minority population is larger, inter-group contact rises, and negative attitudes fall in many instances (Chamberlain, 2011; Fullerton and Dixon, 2009; Steele and Perkins, 2018; Stein et al, 2000).…”
Section: Attitudes Toward Migrantsmentioning
confidence: 99%
“…Fifth, the percentage of the population classified as free black is included. Previous research suggests that the racial environment of a county affected the performance of the abolitionist Liberty Party (Chamberlain, 2011), which grew in some locations from the AASS (Chamberlain, 2018a). It is therefore pertinent to study its effect here, as it too could be a driver of more area, in ESA terms, that leads to the presence of AASS groups.…”
Section: Datamentioning
confidence: 99%